Análise do impacto da sincronia de legendas na qualidade de experiência do usuário - Brito, Jéssica Oliveira (2018)
This work investigates the impact of video subtitle synchronization on user’s quality of experience. As part of this process, a set of exploratory studies were carried out. These studies enabled us to understand how the process of creating, distributing and consuming subtitles for Web videos works, as well as identifying the roles and responsibilities assumed by amateur enthusiasts. Subsequently, we sought to better understand how the synchronization step is performed by these volunteer subtitlers. From what we have learned, we conducted an experiment with a group of 24 users to analyze whether there is a difference in the perception of users’ quality of experience when using the different synchronization directives. The results obtained in our experiment indicate that the worst experience was identified in the sessions whose captions begin after the beginning of the speech of the character, and that when the caption began before or at the same instant of the beginning of the speech, the users better rated it (there were no statistically significant differences). Thus, our results suggest that the perception of users in relation to speech-subtitle synchronization is more noticeable at the beginning than at the end of the subtitle presentation.